2014
DOI: 10.1128/jvi.00913-14
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD8+T Cells and Lymphoid Dendritic Cells in Protection from Ocular Herpes Simplex Virus 1 Challenge in Immunized Mice

Abstract: The development of immunization strategies to protect against ocular infection with herpes simplex virus 1 (HSV-1) must address the issue of the effects of the strategy on the establishment of latency in the trigeminal ganglia (TG). It is the reactivation of this latent virus that can cause recurrent disease and corneal scarring. IMPORTANCEIn the past 2 decades, two large clinical HSV vaccine trials were performed, but both vaccine studies failed to reach their goals. Thus, as an alternative to conventional v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 86 publications
0
18
1
Order By: Relevance
“…In addition, T cell exhaustion was blocked by a recombinant HSV-1 strain expressing CD80 that binds to PD-L1 on the surfaces of DCs (32). Overall, our previous and current findings suggest that CD8␣ ϩ DCs contribute to increased HSV-1 latency and T cell exhaustion (17,22,25,26,28,32). Our previously published studies with regard to the role of LAT in T cell exhaustion were done with mice.…”
Section: Fig 3 Isolation and Functionality Of Purified Cd8 ϩ T Cells mentioning
confidence: 70%
See 3 more Smart Citations
“…In addition, T cell exhaustion was blocked by a recombinant HSV-1 strain expressing CD80 that binds to PD-L1 on the surfaces of DCs (32). Overall, our previous and current findings suggest that CD8␣ ϩ DCs contribute to increased HSV-1 latency and T cell exhaustion (17,22,25,26,28,32). Our previously published studies with regard to the role of LAT in T cell exhaustion were done with mice.…”
Section: Fig 3 Isolation and Functionality Of Purified Cd8 ϩ T Cells mentioning
confidence: 70%
“…Previously, we showed that LAT expression and increased latency correlate with T cell exhaustion (17,22,26,32). We also demonstrated that latency in PD-1 Ϫ/Ϫ mice was lower than that in their wt counterparts (17).…”
Section: Lack Of Effect Of Adoptively Transferred Cd8mentioning
confidence: 98%
See 2 more Smart Citations
“…Isolated tissues were immersed in RNAlater RNA stabilization reagent and stored at Ϫ20°C until processing. The corneas, TG, or brain from each animal were processed for RNA extraction using TRIzol reagent as we described previously (44). Isolated total RNA was reverse-transcribed with random hexamer primers and murine leukemia virus reverse transcriptase provided in a high-capacity cDNA reverse transcription kit (Applied Biosystems) according to the manufacturer's recommendations.…”
Section: Figmentioning
confidence: 99%